PEMANFAATAN BAHAN AJAR E-MODUL BERBANTUAN APLIKASI PREZI PADA MATERI TEKS EKSPLANASI UNTUK SISWA SMP KELAS VIII - Lina Hardiyanti; Via Nugraha; Sary Sukawati (IKIP Siliwangi, 2023)
This research is motivated by the difficulties of students in understanding the material of explanation text, especially in the structure and rules of language, the difficulty of contemplating ideas and ideas into factual written form, such as the source of teaching material that is presented monotonously and is less varied. The purpose of this research is to describe the use of E-Module teaching materials assisted by the Prezi application in writing explanatory text materials. The research method used in this study is descriptive quantitative. The subjects of this research were class VIII C students at SMP Negeri 1 Cikalongwetan. The research results based on observations in the learning process of meetings 1 and 2 reached a percentage of 94% in the